Vanishing landscapes (London : Frances Lincoln, 2008)
Discoveries in a familiar world : the landscape as a photographic object / Friedrich Tietjen ## On visibility : essay / John Berger ## Vanishing landscapes : a vanishing age? / Hans Joachim Schellnhuber ## Why we must act now / Karsten Smid ## Water. Hiroshi Sugimoto ; Elger Esser ; Peter Bialobrzeski ; An-My Lê ; Josef Hoflehner ## Ice. Axel Hütte ; Olaf Otto Becker ; Mette Tronvoll ; Walter Niedermayr ; Michael Kenna ## Plants. Jitka Hanzlová ; Thomas Struth ; Robert Adams ; Giovanni Castell ; Henrik Saxgren ; Joel Sternfeld ## Land. Jem Southam ; Lidwien van de Ven ; Edward Burtynsky ; Karin Apollonia Müller ; Per Bak Jensen.
Onderzoek KASK Professioneel (OFVP)
boek